Political stability as a factor affecting growth in agricultural sub-Saharan African countries - Świerczyńska, Katarzyna; Kaczmarek, Filip; Kryszak, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The agricultural countries of sub-Saharan Africa remain the least economically advanced region of the world, with the relatively lowest quality of life. The agricultural sector plays a particularly important role in the economies of these countries. However, it is underdeveloped as a result of factors such as inadequate agricultural policy, institutional instability, chronic droughts, epidemics, deterioration of the environment, deteriorating infrastructure and insufficient investment in agricultural research in sub-Saharan Africa. The aim of the paper is to examine the impact of political stabilization on the economic growth in these countries. We were also inclined to determine what the interdependences were between political stability and factors important for agricultural activity for both agricultural and non-agricultural sub-Saharan counties in the 1995–2017 period. The methods used in this research included panel models with fixed effects, non-parametric tests and quantile regression. It was found that stabilizing the political situation and lowering the level of conflict risk contributed to the growth of GDP per capita in both agricultural and non-agricultural countries. However, in agricultural countries, it also influenced the modernization of agricultural production methods and a shift in the proportion of agricultural production in the total volume of imports and exports. Furthermore, it was found that political stability contributed to a greater extent to the improvement of GDP per capita in the lowest income countries.

Kraje rolnicze Afryki Subsaharyjskiej pozostają najmniej zaawansowanym gospodarczo regionem świata, o relatywnie najniższej jakości życia. Szczególne znaczenie w gospodarkach tych krajów ma sektor rolniczy. Jest on jednak słabo rozwinięty, co wynika z czynników takich, jak wadliwa polityka rolna, niestabilność instytucjonalna, chroniczne susze, epidemie, degradacja środowiska, pogorszenie infrastruktury oraz niewystarczające inwestycje w badania naukowe w dziedzinie rolnictwa w Afryce Subsaharyjskiej. Celem artykułu jest zbadanie wpływu stabilizacji politycznej na wzrost gospodarczy w tych krajach. Analizowane były też związki między stabilnością polityczną a czynnikami istotnymi z punktu widzenia działalności rolniczej, zarówno w rolniczych, jak i nierolniczych krajach Afryki Subsaharyjskiej w latach 1995–2017. W badaniach wykorzystano modele panelowe z efektami stałymi, testy nieparametryczne oraz regresję kwantylową. Stwierdzono, że stabilizowanie sytuacji politycznej i obniżanie poziomu zagrożenia konfliktem przyczyniało się do wzrostu PKB per capita zarówno w krajach rolniczych, jak i nierolniczych. Niemniej, w krajach rolniczych wpływało także na unowocześnianie metod produkcji rolniczej oraz na zmianę udziału produkcji rolnej w wolumenie importu i eksportu. Ponadto ustalono, że stabilność polityczna przyczyniała się silniej do poprawy PKB per capita w krajach o najniższych dochodach.
Keywords: political stability; sub-Saharan Africa; agriculture; institutional economy; stabilność polityczna; Afryka Subsaharyjska; rolnictwo; ekonomia instytucjonalna